The effect of firm specific characteristics on financial leverage of quoted diversified companies in Nigeria - Abdulkarim, Umar Farouk; Mohammed, Lawal; Mohammed, Aisha Nuhu; Abubakar, Salisu (UUM Press, 2019)
Financial leverage decision by firm continues to attract interest from managers, analysts, researchers, scholars as well as policymakers because of its implications for the firm and its stakeholders. This paper investigates how the complexity of business, firms' dependence on external finance and growth opportunity affects the financial leverage decision among quoted diversified companies in Nigeria. The study took a census of six diversified firms quoted on the Nigerian capital market over the period of 10 years (2008-2017). Descriptive statistics and correlation matrix were employed with panel data analysis using Ordinary Least Square (OLS) robust model to analyse the data. The results from the study revealed that the complexity of business and growth opportunity is positive and significantly influencing the financial leverage of quoted diversified companies in Nigeria, while dependence on the external finance revealed a significantly negative effect on the financial leverage. It is recommended that the management of quoted diversified companies in Nigeria should target an optimal capital structure in line of businesses that their streams of revenue are not positively correlated. This can be achieved by taking advantage of growth opportunities in the industries where they can further diversify their businesses and enhance profit generation.